Proteome analysis of porcine epidemic diarrhea virus (PEDV)‐infected Vero cells. Issue 11 (9th March 2015) - Zeng, Songlin; Zhang, Huan; Ding, Zhen; Luo, Rui; An, Kang; Liu, Lianzeng; Bi, Jing; Chen, Huanchun; Xiao, Shaobo; Fang, Liurong
<x xml:space="preserve">Abstract</x> Porcine epidemic diarrhea virus (PEDV) causes an acute, highly contagious, and devastating viral enteric disease with a high mortality rate in suckling pigs. A large‐scale outbreak of PED occurred in China in 2010, with PEDV emerging in the United States in 2013 and spreading rapidly, posing significant economic and public health concerns. In this study, LC–MS/MS coupled to iTRAQ labeling was used to quantitatively identify differentially expressed cellular proteins in PEDV‐infected Vero cells. We identified 49 differentially expressed cellular proteins, of which 8 were upregulated and 41 downregulated. These differentially expressed proteins were involved in apoptosis, signal transduction, and stress responses. Based on these differentially expressed proteins, we propose that PEDV might utilize apoptosis and extracellular signal regulated kinases pathways for maximum viral replication. Our study is the first attempt to analyze the protein profile of PEDV‐infected cells by quantitative proteomics, and we believe our findings provide valuable information with respect to better understanding the host response to PEDV infection.